Self-Assembled STrap for Global Proteomics and Salivary Biomarker Discovery - Lin, Yi-Han; Eguez, Rodrigo Vargas; Torralba, Manolito G; Singh, Harinder; Golusinski, Pawel; Golusinski, Wojciech; Masternak, Michal; Nelson, Karen E; Freire, Marcelo; Yu, Yanbao (Journal of proteome research, 2019)
Clinical biomarkers identified by shotgun proteomics require proteins in body fluids or tissues to be enzymatically digested before being separated and sequenced by liquid chromatography-tandem mass spectrometry. How well peptide signals can be resolved and detected is largely dependent on the quality of sample preparation. Conventional approaches such as in-gel, in-solution, and filter-based digestion, despite their extensive implementation by the community, become less appealing due to their unsatisfying protein/peptide recovery rate, lengthy sample processing, and/or lowcost-effectiveness. Suspension trapping has recently been demonstrated as an ultrafast approach for proteomic analysis. Here, for the first time, we extend its application to human salivary proteome analyses. In particular, we present a simple self-assembled glass fiber filter device which can be packed with minimal difficulty, is extremely cost-effective, and maintains the same performance as commercial filters. As a proof-of-principle, we analyzed the whole saliva from 8 healthy individuals as well as a cohort of 10 subjects of oral squamous cell carcinoma (OSCC) patients and non-OSCC subjects. Label-free quantification revealed surprisingly low interindividual variability and several known markers. Our study provides the first evidence of an easy-to-use and low-cost device for clinical proteomics as well as for general proteomic sample preparation.